Korelasi Stres dan Aktivitas Fisik dengan Tekanan Darah pada Penderita Hipertensi Essensial - Miko Eka Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Hypertension is a global health problem. The prevalence of hypertension in Indonesia is 26.5% and there have been 9.4 million people out of 1 billion people in the world die from cardiovascular disorders. Data from the Jambi Provincial Health Office shows that hypertension ranks 2nd out of the 5 biggest diseases in Jambi. factors that affect blood pressure such as; age, stress, ethnicity, gender, daily variation, medication, activity, weight, and smoking. The purpose of this study was to determine the correlation between stress and physical activity with blood pressure. The method of this research is in essential hypertensive patients in the Working Area of Talang Bakung Health Center, Jambi City. This research is a quantitative study with a cross sectional approach. The study was conducted on 1 - 11 August 2018 with a sample of 41 people, purposive sampling technique. Data collection is done using guided interviews using a questionnaire. The results of the study were analyzed using the chi square test. The results showed that the majority of respondents 35 (85.4%) experienced hypertension, some respondents 24 (58.5%) experienced stress and most 26 (63.4%) respondents had heavy physical activity. The results of statistical tests were obtained (p-value 0.003 & 0.018) p-value <0.05, meaning that there was a significant relationship between stress and physical activity with blood pressure in essential hypertensive patients. The conclusion of the study is that, as severe as stress is deep in patients with hypertension, the higher the blood pressure and the more severe physical activity carried out will cause an increase in blood pressure. It is expected that nurses can provide health education to people with hypertension in order to avoid stress and reduce physical activity so there is no increase in blood pressure